Black designers in American fashion - Way, Elizabeth (Bloomsbury Visual Arts, 2021)
Anonymous histories -- In the atelier : modistes and independent designers -- Into the mainstream : Seventh Avenue and beyond -- The star designer : national and international impact
Includes bibliographical references and index
Keywords: Modeschöpferin; Modeschöpfer; Schwarze; Amerika; Fashion / United States / History; African American fashion designers / History; History of fashion; Electronic books